Analysis of Factors Affecting Individuals’ Online Consumer Credit Behavior: Evidence From China - Zhao, Huiying; Peng, Huaxin; Li, Wanqi (Frontiers in Psychology, 2022)
In the past two decades, a growing number of Chinese young adults utilize online consumer credit to satisfy their increasing consumption demand. Although it is indeed boosting consumer markets, it has also caused many serious social problems. A number of previous studies discussed the authentication mechanism and legal supervision of online lending from a legal or economic perspective, and a small number of scholars explored factors affecting individuals’ online consumer credit from the perspective of behavioral psychology. Based on the Triandis model and existing studies on online lending, this paper constructs a theoretical model for the formation of individuals’ online consumer credit. It then adopts SmartPLS 3.00 to analyze the data set that involves 302 respondents in total. This research found that affect, facilitating conditions, perceived consequences and social factors have a significant impact on individuals’ online consumer credit. The findings of this study have political and practical implications. First, they can contribute to the rational consumption by China's young generation and promote the sound development of online consumer credit. In the meantime, this study also helps online consumer credit platforms to provide better services and improve public relations.